Theory Building - Shepherd, Dean A.; Suddaby, Roy (Journal of Management, 2017)
Building theories is important for advancing knowledge of management. But it is also a highly challenging task. Although there is a burgeoning literature that offers many theorizing tools, we lack a coherent understanding of how these tools fit together—when to use a particular tool and which combination of tools can be used in the theorizing process. In this article, we organize a systematic review of the literature on theory building in management around the five key elements of a good story: conflict, character, setting, sequence, and plot and arc. In doing so, we hope to provide a richer understanding of how specific theorizing tools facilitate aspects of the theorizing process and offer a clearer big picture of the process of building important theories. We also offer pragmatic empirical theorizing as an approach that uses quantitative empirical findings to stimulate theorizing.